Using a Resident-Led School Outreach Program to Improve Knowledge of All-Terrain Vehicle Safety. Issue 2 (February 2021) - Jeffries, Kristyn; Burks, A. Reid; Nichols, Michele; Farmer, Julie; Shah, Nipam; Jennissen, Charles A.; Denning, Gerene M.; Monroe, Kathy
Abstract : Background: During the past decade, all-terrain vehicle (ATV)–related injuries treated in US emergency departments decreased by 33%, down to approximately 100, 000 injuries in 2016. In comparison, the number of children evaluated for ATV injuries in the Children's of Alabama emergency department more than doubled between 2006 and 2016, counter to the national trend. The American Academy of Pediatrics guidelines state that ATV operators should be at least 16 years old; however, children younger than 16 continue to represent almost one-third of all ATV-related injuries nationwide, and nearly all of the injuries to children in Alabama. Methods: Using surveillance data from the Children's of Alabama hospital electronic medical record database, several Alabama counties near Birmingham were identified as having an increased number of children with ATV-related injuries in 2016. The Safety Tips for ATV Riders (STARs) program, developed in Iowa, was provided to middle school students in these counties by pediatric residents. Surveys were anonymously administered to children before and after the program and included information about demographics, knowledge of safe ATV practices, and the likelihood of using the education afterward. Results: In total, 525 students participated in January 2019; their ages ranged from 11 to 15 years and the proportion of males and females was equivalent. More than 50% of the children reported riding ATVs in the last 12 months, and of these riders, 47% reported never wearing a helmet when riding. Initially, only 20% of the overall participants knew ATVs were not intended for passengers, 20% knew the recommended engine size for their age, and 57% knew that Alabama law prohibits riding on public roads. After education, this increased to 91%, 90%, and 89%, respectively. Before the STARs program, only 6% knew all three correct answers, whereas 80% answered all of the questions correctly on the postprogram survey. After the program, 34% reported they were very likely/likely to use this information in the future. Conclusions: The STARs program dramatically improved short-term ATV safety knowledge, and many participants reported they were likely to subsequently use the safe practices presented. School-based programs, such as STARs, may help increase ATV safety awareness and change behaviors in high-risk age groups. This training may be successfully provided by various motivated individuals, including medical residents. Abstract : This article describes a community outreach injury prevention program aimed at middle school children and all-terrain vehicle safety. The program was conducted in middle schools in a southern state, and pediatric resident physicians provided the education. All-terrain vehicle injuries and deaths are an all-too-common occurrence in rural southern states and occur in all ages, but have highest fatality rates in the middle school population.